Fundamental laboratory mathematics : equired calculations for the medical laboratory professional - Buckingham, Lela
Conquer the math skills essential for the laboratory ... and reduce the anxieties math often induces! Step by step, skill by skill ... you'll progress from simple to complex calculations, building your proficiencies and testing them along the way. Perfect for classroom, clinical, and professional success!Begin by reviewing the basics-algebra, scientific notation, and units of measure. Then, progress to dilutions and standard curve calculations and logarithms. You'll also find easy-to-understand explanations and real-world examples that show you how to apply what you've learned to enzyme chemistr